Interactive Buckling of Thin-Walled Beams with Open and Closed Cross-Sections - Kołakowski, Z. (Engineering Transactions, 1989)
Influence of the interaction of nearly simultaneous buckling modes on the postbuckling behaviour of thin-walled beams with imperfections is studied. The investigation is concerned with thin-walled closed and open cross-section elastic beams under an axial compression and a constant bending moment. The beams are assumed to be simply supported at the ends. The asymptotic expansion established by BYSKOV and HUTCHINSON [1] is employed in the numerical calculations in the form of the transition matrix method. The paper’s aim is to achieve the improved study of the equilibrium path in the initial postbuckling behaviour of imperfect structures in which the effect of the interaction of a few buckling modes would be included. The calculations are carried out for several types of beams.